Niobium Pentachloride Catalyzed Multicomponent Povarov Reaction - Sacoman Torquato da Silva, Bruno Henrique [UNESP]; Martins, Lucas Michelao [UNESP]; da Silva-Filho, Luiz Carlos [UNESP] (Georg Thieme Verlag Kg, 2012)
A single-step method for the synthesis of furan-and pyranoquinoline derivatives through multicomponent Povarov reactions between aniline derivatives, benzaldehyde and two different enol ethers (2,3-dihydrofuran and 3,4-dihydropyran) using niobium pentachloride as catalyst under mild conditions, providing good yields and high diastereoselectivity, is described.
Keywords: niobium pentachloride; multicomponent Povarov reaction; furanoquinolines; pyranoquinolines; Lewis acid